Hungarian Monitoring, 2 May 1990 . [Magyar rádiófigyelő], 1990. május 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Boris Yeltsin's operation in Spain - Reduction in the number of troops in Warsaw - Egyptian-Syrian summit in Damascus Domestic Affairs: - First democratically elected parliament starts its work, ceremonial speeches - Árpád Göncz is the President of Hungary - György Szabad is the Speaker of Parliament - Miklós Németh resigns - József Antall receives the mandate to form the new government - Increase in the number of refugees from Transylvania due to a rumor of future visa restrictions - Alliance of Young Democrats (Fidesz) demonstration in support of Lithuanian independence Economy: - Hungarian National Bank devaluates the Forint in relation to the Czech koruna - Difficulties in selling the Young Pioneers' leftover equipment Külpolitika: - Jelcint megműtik Spanyolországban - Csapatlétszám csökkentés Varsóban - Egyiptomi - Szír csúcstalálkozó Damaszkuszban Belpolitika: - Munkához lát a szabadon választott parlament, ünnepi beszédek - Göncz Árpád az új államfő - Szabad György a házelnök - Lemondott Németh Miklós - Antall József átveszi a kormányalakítási megbízást - Egyre több menekült érkezik Erdélyből Magyarországra a tervezett vízumkényszer rémhírének következtében - Litvánia függetlenségéért tüntet a Fidesz Gazdaság: - A Magyar Nemzeti Bank leértékelte a forintot a cseh koronához képest - Nehézségek a megmaradt úttörő kellékek eladásánál